Numerical simulation on the rffect of concentration on premixed ch4/co2/air explosion characteristics - Nur Aqidah, Muhammad Harinder Khan; Siti Zubaidah, Sulaiman; Izirwan, Izhab; Siti Kholijah, Abdul Mudalip; Rohaida, Che Man; Shalyda, Md Shaarani; Zatul Iffah, Mohd Arshad; Rafiziana, Md Kasman; Sarina, Sulaiman (Universiti Malaysia Pahang, 2019)
In this study, a numerical simulation on the premixed CH4/CO2/air (methane/carbon dioxide/air)mixture explosion characteristics was conducted by using the FLame ACcelaration Simulator (FLACs) software. The domain used in the 20 L spherical vessel with 0.808 m diameter. The effect of various equivalence ratios on the explosion characteristics such as the explosion pressure, Pex, maximum explosion overpressure, Pmax, the maximum rate of pressure rise, (dP/dt)max and gas deflagration index, KG, were studied. For this purpose, the mixture concentrations range from equivalence ratio (ER) 0.8 to 1.5 (9.6 to 18% vol/vol) were considered. From this study, the explosion pressure, Pex, maximum explosion overpressure, Pmax, and the maximum rate of pressure rise, (dP/dt)max, at various ER was the maximum at a slightly rich concentration (ER=1.2). At lean and rich mixtures, the Pex, Pmax, (dP/dt)max and KG decreases. It can be said that, at ER=1.2, the role of thermal-diffusive instability and its effect on the flame speed during the pressure development process had causes the diffused methane, CH4, to react further into the flame front, which significantly increases the mixture mass burning rate and flame speed thus improving the mixture explosion characteristics. From this study, the flame was also found to propagates the fastest at ER=1.2 due to the incomplete combustion process caused by the insufficient and excess CH4 present in the lean and rich mixtures. The CH4/CO2/air mixtures studied in this study were also found to have the highest level of hazard potential when exploded.